The rule of maintaining the system and its relation to the maintenance of the political system; with emphasis on Imam Khomeini’s juridical thought - Seyed Zia Mortazaviz (علوم سیاسی, 2019)
The aim of this study is to investigate and identify the rule of “maintenance of the system “and its relation with the protection of "political system” in juridical thought of Imam Khomeini .The method of this research is descriptive - analytic and in order to study the sovereignty and generality of maintenance the social system , the reason of the necessity and sovereignty of the system , maintenance the system in Islamic jurisprudence , the association of the maintenance of the general system and the special system , the maintenance of the political system and the maintenance of the regime of Islam were studied . The results showed that imam Khomeini’s order to maintain the existing political system with the maintenance of the social system, and preserve the status and face and face of Islam, consider maintaining the Islamic republic system the most important task or the most important religious duty. The origin of this task should be analyzed in direct connection maintenance of the system with performance of the system, and it should be understood by people’s fealty to protect the system against enemies.